Maladaptive coping among military-connected adolescents: Examining combined risk using QCA - Gilreath, Tamika D.; Montiel Ishino, Francisco A.; Sullivan, Kathrine S.; Okoror, Titilayo A. (Frontiers in Psychology, 2022)
Military-connected students in public schools face a unique set of stressors that may impact their wellbeing and academic functioning. Twenty-four youth in the 7th to 12th grades who had an active-duty parent (mother or father) serving in the U.S. Armed Forces were interviewed. Participants completed a qualitative interview while actively completing a Life History Calendar (LHC) to mark deployment and family military service milestones and discuss how they impacted the youth respondent. This study used Qualitative Comparative Analysis (QCA) to explore the interplay and combination of specific stressors related to relocation and deployment experiences among adolescents, and to determine key factors associated with maladaptive outcomes. The results of the QCA analysis identified bullying experiences and negative experiences with other military-connected youth as conditions that are associated with maladaptive coping. Chronic and acute stressors in adolescence are established risk factors for mental, emotional, and behavioral problems in the short and long-term including suicidality, substance use and abuse, and substance use disorders. Through qualitative inquiry we were able to identify specific contextual details related to maladaptive coping that can be used to further refine areas of focus for research, prevention, and interventions for military-connected adolescents.